Multi-territorial licensing of rights in musical works for online use in the internal market: Directive 2014/26/EU. (17th June 2019) - Prieto, Laura
This paper will consider questions around the Directive 2014/26/EU concerning the multi-territorial licensing of rights in musical works for online use in the internal market, considering the digital economy and the context of the Digital Agenda for Europe and the Europe 2020 Strategy aiming for smart, sustainable and inclusive growth, and the Article 167 and others of the Treaty on the Functioning of the European Union (TFEU). The paper will consider the need to provide of coordination of national rules to avoid the inefficiencies in the exploitation of copyright and related rights across the internal market, looking for the benefit of rightholders and users, and the need of metadata systems for an effective aggregation of repertories. The paper will also consider the derogation for online music rights required by a broadcaster to communicate or make available to the public its radio and television programs.